2019
DOI: 10.1021/acs.biomac.9b01297
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Helical Modular Polypeptide-Based Hydrogels as Synthetic Extracellular Matrices for Cell Culture

Abstract: Expanding the toolkit of modular and functional synthetic material systems for biomimetic extracellular matrices (ECMs) is needed for achieving more predictable and characterizable cell culture. In the present study, we engineered a synthetic hydrogel system incorporating poly­(γ-propargyl-l-glutamate) (PPLG), an N-carboxy anhydride polypeptide with a unique α-helical secondary structure. PPLG macromers were cross-linked into poly­(ethylene glycol) (PEG) networks to form hybrid polypeptide-PEG hydrogels. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…A limitation of our polymerization scheme is that hydrogel degradability and elasticity are coupled, meaning that changing one changes the other. To independently tune these two parameters would require the implementation of multi-arm PEG chemistry to gain independent control over these parameters [66][67][68][69] and is of interest in future studies. While we anticipate elasticity played a minor role in influencing cancer cell fate, we found that ligand density had a significant influence on cancer cell phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of our polymerization scheme is that hydrogel degradability and elasticity are coupled, meaning that changing one changes the other. To independently tune these two parameters would require the implementation of multi-arm PEG chemistry to gain independent control over these parameters [66][67][68][69] and is of interest in future studies. While we anticipate elasticity played a minor role in influencing cancer cell fate, we found that ligand density had a significant influence on cancer cell phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1–4 ] To date, sol–gel transitions (gelation) have been studied and utilized for the fabrication of materials like soft hydrogels in tissue engineering and also have high relevance for understanding the onset and development of protein‐aggregation diseases. [ 1–8 ] Recently, there is a growing interest in developing materials formed by liquid–liquid phase separation (LLPS), which is found at the heart of a range of biological processes connected to biological function and malfunction. [ 9–13 ] The processes underlying the formation of liquid‐state and gel‐state proteins can involve different physicochemical mechanisms, and liquid‐state materials are a key category of functional biological structures as well as an important complement of conventional solid or gel materials.…”
Section: Introductionmentioning
confidence: 99%
“…The main efforts on engineered ECM in the biomedical field have been focused on the use and stimulation of pluripotent stem cells, which are special cells that have the ability to perpetuate themselves through a mechanism of self-renewal and to generate diverse types of cells through differentiation processes [15][16][17]. Nevertheless, osteoblasts [18], skeletal muscle cells [18], and endothelial cells [20] have been also studied.…”
Section: Polysaccharide-based Porous Materials For Tissue Engineeringmentioning
confidence: 99%
“…Porous materials from polysaccharides have been used as extracellular matrices (ECM) in tissue engineering in order to generate diverse types of cell lineages, promoting regeneration [15,16], for instance, in stem cells [17], osteoblasts [18], skeletal muscle cells [19], and endothelial cells [20]. In the biomedical field, aerogels from different sources have found applications as implantable devices, dressings for wound healing, synthetic bone grafts, carriers for different drugs, biosensing, and biomedical imaging [6,21].…”
Section: Introductionmentioning
confidence: 99%